The Use of Authentic Reading Materials and Cooperative Learning Strategy to Improve Reading Comprehension Ability of Vocational School Students - Suparman, Ujang (Jurnal Pendidikan Progresif, 2022)
The objective of the research is to investigate the correlation between students’ perception on authentic materials and cooperative strategy on their reading achievement. Method: Three hypotheses were tested: a. perception on authentic materials and reading comprehension; b. perception on cooperative strategy and reading comprehension, and c. perception on authentic materials and cooperative strategy toward reading achievement. Findings: The reliability of reading test was rii = 0.96; perception on authentic materials was rii = 0.913; and that of the cooperative strategy was rii = 0.862. Conclusion: a. There is a positive correlation between perception on X1 and Y, Y = 11.046 + 0.270; X1 coefficient correlation r13 = 0.431. b. There is a significant effect of X2 on Y, Y = 11.350 + 0.625, X2 coefficient correlation r23 = 0.411. c. There is significant effect of X1 on X2, X1 = 5.314 + 0.974, X2 coefficient correlation r12 = 0.436.Keywords: authentic materials, cooperative strategy, comprehension achievement.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202223